USP25 inhibition ameliorates Parkinson’s disease by restoring mitophagy - Yanqi Xu; Keshuo Jin; Jiaqing Chen; Zhongding Li; Zhenhu Zhu; Xian Su; Jiangyun Shen; Bincheng Zhou; Zijun Cao; Liyan Lou; Deyu Deng; Jianzhao Zhang; et al. (Proceedings of the National Academy of Sciences, 2026)
Parkinson’s disease (PD) is a progressive neurodegenerative disease that casts a significant shadow over global health and the identification of therapeutic targets for PD will empower more effective clinical treatment. The gene encoding the deubiquitinating enzyme USP25 has been identified as a susceptible locus for PD, but the role of USP25 in PD remains unknown. In this study, we found that USP25 exacerbated dopaminergic neuronal loss and motor deficits in murine models of PD by sabotaging the mitophagy machinery. USP25 physically interacted with the autophagy receptor optineurin and disrupted its linkage with K63-specific polyubiquitin chains, leading to impaired mitophagy and the accumulation of damaged mitochondria. Genetic ablation or pharmacological inhibition of USP25 significantly restored mitophagy and thereby impeded the neurodegenerative progression in PD model mice. Collectively, our results unravel a pivotal role of USP25 in PD and identify USP25 as a pharmacological target for the development of PD drugs.